Multidimensional Analysis of Charitable Behavior: Integration of Altruism, Religiosity, and Economy in Global Social Context - Anggraeni, Yuyun; Kuklienė, Lina (Potret Pemikiran, 2024)
This research employs the Theory of Planned Behavior approach to analyze factors influencing charitable behavior in Bulukumba Regency. The background of this research is the importance of Islamic philanthropy, such as charitable giving, in addressing social inequality and improving collective welfare. This study aims to identify the influence of altruism, religiosity, and economic dimensions on charitable behavior, focusing on multidimensional integration. The research involved 110 respondents selected through purposive sampling technique. Data were collected through online questionnaires and analyzed using multiple linear regression. Results show that religiosity has the most dominant influence on charitable behavior, followed by altruism and economics. The determination coefficient of 76% indicates that the three independent variables significantly influence charitable behavior. This research confirms the importance of religion-based subjective norms in motivating philanthropy and highlights the relevance of local values in strengthening community participation. These findings provide important implications for philanthropic institutions and local governments in designing inclusive and sustainable policies.